Characteristics of Effective Elementary Mathematics Instruction: A Scoping Review of Experimental Studies - Branko Bognar; Sanela Mužar Horvat; Ljerka Jukić Matić (Education Sciences)
Considering that the teaching of mathematics in elementary school is an important prerequisite for the development of mathematically literate citizens, it is essential to identify what makes it effective. The aim of this study is to determine the characteristics of effective interventions in elementary school mathematics education. To this end, a scoping review was conducted that included 44 experimental studies published between 2014 and 2023. Through a qualitative analysis of the intervention descriptions, we identified 27 characteristics, which were categorized into nine thematic units. We found that, on average, seven characteristics were used per intervention. The results of this study suggest that effective elementary school mathematics instruction should foster students’ conceptual understanding and procedural fluency through problem-solving, active learning, and mathematical games. This can be achieved through a dynamic alternation of whole-class instruction and cooperative and individual learning with the use of manipulatives and visualizations to reach the level of abstraction. Considering that the analyzed interventions rarely addressed students’ common errors and critical thinking, future research could focus on these aspects in elementary school mathematics education.